Fiber connectivity density in subcortical stroke patients with behavioral dysexecutive symptoms - Lisha Wang; Lin Shi; Edward S. Hui; Yan Liang; Wai-Kwong Tang (Brain Research Bulletin)
Subcortical stroke induces widespread connectivity changes between cortical and subcortical regions, which may underpin the ensuing behavioral dysexecutive symptoms. This study therefore investigated the cortical structural connectivity that were related to behavioral dysexecutive symptoms using fiber connectivity density (FiCD) mapping, an approach which combines white matter (WM) fiber tractography and cortex reconstruction. The relationships between cortical structural connectivity of significant clusters and its corresponding cortical thickness (CT), and clinical variables were also evaluated based on region-of-interest analysis. Sixty-four subcortical stroke patients with high-resolution T1-weighted imaging and diffusion tensor imaging were enrolled and the behavioral dysexecutive symptoms were assessed using the dysexecutive questionnaire. The FiCD of the left superior parietal gyrus was positively associated with cognitive executive processing (CTT1 time, r = 0.570, p = 0.047; CVFT total correct, r = 0.582, p = 0.047; CVFT total response, r = 0.605, p = 0.040). Similary, the FiCD of the right superior parietal gyrus was also positively associated with cognitive executive processing, (CTT1 time, r = 0.639, p = 0.034). Conversely, negative correlations were observed between the FiCD and CT of the right (r = -0.612 p = 0.045) superior parietal gyrus.